Everyday Encounters in the Shopping Mall: (Un)Making Boundaries in the Divided Cities of Johannesburg and Mostar. Issue 1 (2nd January 2019) - Aceska, Ana; Heer, Barbara
ABSTRACT: The many studies that see shopping malls as places of power, control and exclusion have often neglected the potential of malls as places of encounters. Drawing on ethnographic data from the divided cities of Johannesburg in South Africa and Mostar in Bosnia–Herzegovina, we examine the ways in which urban dwellers who enter the mall from a marginalised position – poor black urban dwellers at a regional, middle class and white-dominated mall in Johannesburg and Bosniak city dwellers at a mall located in the Croat part of Mostar – use the mall, what kind of relations they build to others and how they rework boundaries of race, class, religion and ethnicity at the mall. Rather than being spaces that strengthen and reproduce centre–margins relations, urban dwellers appropriate them as places where these relations become reworked.